Pelatihan Membangun Integritas Anak Remaja pada Revolusi Mental di Desa Bunut Sebrang - Subagiharti, Heni; Handayani, Diah Syahfitri; Herawati, Tuti (PASAI : Jurnal Pengabdian kepada Masyarakat, 2022)
Training to Build Youth Integrity in the Mental Revolution in Bunut Village aims to achieve an evaluation mechanism, so that it can be seen how far the progress and efforts of these activities have been achieved. Likewise in this activity it also refers to the goals to be achieved, both the targets to be achieved in this activity and the final goal in the form of positive change impacts that arise with this activity. The positive results or impacts that arise can be in the form of changes in behavior or attitudes that are good, especially teenagers. High integrity will produce people who are disciplined and care about their surroundings and have integrity values that are the difference between people who have integrity or not. A person with a character of integrity will become a superior human being and will withstand the trials of life that he faces.